Combined Volar and Dorsal Approach for Fixation of Comminuted Intra-Articular Distal Radial Fractures - Medlock, G.; Smith, M.; Johnstone, A. J. (Journal of Wrist Surgery, 2018)
Purpose Multifragmentary intra-articular fractures displaced in multiple planes are a challenge. We use a reproducible technique of fracture and articular reduction using an initial volar approach targeting reduction in the volar lunate facet first with plate and unicortical locking screws. This creates a template for reduction in dorsal fragments through a dorsal approach. Our study investigated the radiological, clinical, and functional outcomes of patients treated with this technique.Materials and Methods We reviewed the postoperative radiographs and notes of 18 patients that had this method of fixation between the years 2008 and 2015, the mean age being 43. These patients were reviewed functionally on average 2 years and 3 months following their definitive operation.Results Normal alignment and length to the distal radius were restored with on average a 0.6 mm articular step. The average range of motion was 64% and preservation of grip strength was 71% compared with the uninjured wrist. Functional assessment averages were 29 for both the quick Disabilities of the Arm, Shoulder and Hand (DASH) and for Patient Rated Wrist Evaluation. The modified system of Green and O'Brien had results of good in 10, fair in 7, and poor in 1. With respect to the Gartland and Werley system, three patients had an excellent result, four had a good result, six had a fair result, and five had a poor result. The mean arthritic grading was 1 (grading 0–3) according to Knirk and Jupiter.Conclusion This reproducible technique provides an option for these devastating fractures providing a functioning wrist with all of the patients returning to their original form of employment.
Keywords: distal radius fracture; internal fixation; dual approach; fracture specific